2015
DOI: 10.1002/jnr.23698
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells attenuate peripheral neuronal degeneration in spinocerebellar ataxia type 1 knockin mice

Abstract: Spinocerebellar ataxia type 1 (SCA1) is a devastating neurodegenerative disorder in which an abnormally expanded polyglutamine tract is inserted into causative ataxin-1 proteins. We have previously shown that SCA1 knockin (SCA1-KI) mice over 6 months of age exhibit a degeneration of motor neuron axons and their encasing myelin sheaths, as reported in SCA1 patients. We examined whether axon degeneration precedes myelin degeneration or vice versa in SCA1-KI mice and then attempted to mitigate motor neuron degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…For MSCs in dental tissues such as human dental pulp stem cells (hDPSCs), one report showed that hDPSCs cannot mature into functional neurons (Aanismaa et al, ), whereas a more recent study was able to demonstrate electrophysiological characteristics of functional neurons derived from hDPSCs (Gervois et al, ). In general, more consistent findings on MSCs are that they tend to play a supporting role in neurogenesis by preventing cell apoptosis, providing neurotropic factors, and differentiating into glial cells instead of becoming neurons (Chen, Wang, Lu, Zhang, & Chopp, ; Hofstetter et al, ; Huang, Snyder, Cheng, & Chan, ; Kopen, Prockop, & Phinney, ; Lee et al, ; Mantovani, Terenghi, & Shawcross, ; Mieda et al, ; Sakai et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…For MSCs in dental tissues such as human dental pulp stem cells (hDPSCs), one report showed that hDPSCs cannot mature into functional neurons (Aanismaa et al, ), whereas a more recent study was able to demonstrate electrophysiological characteristics of functional neurons derived from hDPSCs (Gervois et al, ). In general, more consistent findings on MSCs are that they tend to play a supporting role in neurogenesis by preventing cell apoptosis, providing neurotropic factors, and differentiating into glial cells instead of becoming neurons (Chen, Wang, Lu, Zhang, & Chopp, ; Hofstetter et al, ; Huang, Snyder, Cheng, & Chan, ; Kopen, Prockop, & Phinney, ; Lee et al, ; Mantovani, Terenghi, & Shawcross, ; Mieda et al, ; Sakai et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…Chang et al [ 277 ] showed that intravenous injection of MSCs in SCA2 mice improved rotarod performance and Purkinje cell survival, while intracranial transplantation failed to achieve these neuroprotective effects [ 277 ]. Intrathecal injection of MSCs and intravenous injection of MSC-conditioned medium ameliorated both cerebellar pathology and behavior phenotypes in different mouse models of SCA1 and SCA3 [ 275 , 276 , 278 , 291 ]. The first phase 1/2 clinical trials to evaluate the safety, tolerability, and efficacy of intrathecal injection or intravenous administration of MSCs from healthy donors in polyQ SCA patients have been performed [ 292 295 ].…”
Section: Stem Cell Therapiesmentioning
confidence: 99%
“…Both axons and myelin degenerate in old SCA1-KI mice [23]. We recently showed that intrathecal injection of MSCs relieves the degeneration of axons and myelin in SCA1-Tg mice [16]. In the current study, we reproduced these morphological improvements using MSC-CM rather than MSCs themselves.…”
Section: Discussionmentioning
confidence: 64%